NUR-SULTAN MAINSTREAM SCHOOL TEACHERS’ KNOWLEDGE OF AND ATTITUDES TOWARDS ADHD - Akatayeva, Aizhan (Nazarbayev University Graduate School of Education, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common neurodevelopmental disorders among school-aged children, with a prevalence of about 5%. ADHD-related behaviour is mostly observed in a school setting as children spend most of their time at school. Therefore, teachers’ role is significant as they are the first to recognize the characteristics of children with ADHD and refer them for assessment. Moreover, their attitude and support are important in leading to successful student outcomes. Teachers’ limited or lack of knowledge of ADHD can result in unfavorable attitudes towards students with ADHD, which can lead to negative academic and non-academic consequences for such students. This study aimed to explore mainstream school teachers’ knowledge of and attitudes towards students with ADHD, and identified teacher-related background factors that affect their knowledge and attitudes. The data was collected through an online survey using ADHD-specific knowledge and attitudes of teachers (ASKAT), which consists of two scales: Scale for ADHD-specific knowledge (SASK) and Scale of ADHD-specific attitudes (SASA). Overall, 167 teachers from ten schools in Nur-Sultan participated in this study. The study findings revealed that teachers’ knowledge about ADHD was low and that they held slightly negative attitudes towards ADHD. Moreover, it was found that additional training on ADHD and experience with students with ADHD did significantly predict the level of knowledge about ADHD, whilst the level of knowledge about ADHD, additional training on ADHD, and age were significant predictors of teachers’ attitudes towards ADHD. It is also important to note that the results of the current study indicated a positive correlation between teachers’ knowledge of and attitudes towards ADHD. Although teachers’ disposition towards ADHD was negative, they expressed more favorable attitudes in relation to the desire for more training on ADHD. These results suggest the need for in-service training and professional development regarding ADHD for Kazakhstani mainstream school teachers. In addition to this, it was suggested to conduct more research on ADHD in Kazakhstan to understand better to what extent teachers of different regions of Kazakhstan know about ADHD and how they perceive children with ADHD.
Keywords: ADHD; attitude; mainstream schools; Attention Deficit Hyperactivity Disorder; Type of access: Open Access